ChemInform Abstract: Core—Shell Nanoparticles: Synthesis and Applications in Catalysis and Electrocatalysis. Issue 50 (December 2015) - Gawande, Manoj B.; Goswami, Anandarup; Asefa, Tewodros; Guo, Huizhang; Biradar, Ankush V.; Peng, Dong‐Liang; Zboril, Radek; Varma, Rajender S.
Abstract: Review: 476 refs.